The Design of Baby Fish Counter with Parallel Sensors - Kudang B. Seminar (PERTETA, 2000)
This paper describes the design of baby fish counter with parallelsensors to enhance the speed of counting process. This design is developed from the previous baby Jish counter with a single sensor. The counter with 0 single sensor has only one outlet channel through which baby fishes are being own and counted. The new baby fish counter is designed to have multiple outlet channels, each of which is equipped with a sensor to enable uparullel counting process, and thus increasing the counting speed.